2013
DOI: 10.1051/0004-6361/201321399
|View full text |Cite
|
Sign up to set email alerts
|

Shocks in dense clouds

Abstract: Context. Grain-grain processing has been shown to be an indispensable ingredient of shock modelling in high density environments. For densities higher than ∼10 5 cm −3 , shattering becomes a self-enhanced process that imposes severe chemical and dynamical consequences on the shock characteristics. Shattering is accompanied by the vaporization of grains, which can, in addition to sputtering, directly release SiO to the gas phase. Given that SiO rotational line radiation is used as a major tracer of shocks in de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 46 publications
7
56
0
Order By: Relevance
“…To compare with the observed CO SLEDs, we then employ a post-processing treatment based on the LVG approximation, following the method used in Gusdorf et al (2012), Anderl et al (2014), and Gusdorf et al (2015). In our modelling, the effects of grain-grain interactions (e.g., Guillet et al 2011;Anderl et al 2013) are not considered, since these effects play an important role only for high density and shock velocity (n pre > 10 4 cm −3 and v s > 20 km s −1 ) cases. Finally, we note that reducing the input metallicity by a factor of 2 to match the LMC value (∼0.5 Z ⊙ ; e.g., Pagel 2003) would not change our main results.…”
Section: Paris-durham Shock Modellingmentioning
confidence: 99%
“…To compare with the observed CO SLEDs, we then employ a post-processing treatment based on the LVG approximation, following the method used in Gusdorf et al (2012), Anderl et al (2014), and Gusdorf et al (2015). In our modelling, the effects of grain-grain interactions (e.g., Guillet et al 2011;Anderl et al 2013) are not considered, since these effects play an important role only for high density and shock velocity (n pre > 10 4 cm −3 and v s > 20 km s −1 ) cases. Finally, we note that reducing the input metallicity by a factor of 2 to match the LMC value (∼0.5 Z ⊙ ; e.g., Pagel 2003) would not change our main results.…”
Section: Paris-durham Shock Modellingmentioning
confidence: 99%
“…The final considered ages range from a few tens to around fifteen thousand years. Our grid also includes a few stationary models including the effects of grain-grain interactions, as presented in Guillet et al (2011); Anderl et al (2013), and already used in Anderl et al (2014); Leurini et al (2014a).…”
Section: Constraining Shock Modelsmentioning
confidence: 99%
“…Interestingly, the transfer of Si from the core to the mantles in the form of SiO was also considered by Anderl et al (2013) in the context of denser shock models. Indeed, for pre-shock densities above 10 5 cm −3 , the effect of grain-grain interactions cannot be neglected in shock models, as shown by Guillet et al (2011).…”
Section: Employing Shock Models: Sio Chemistrymentioning
confidence: 99%
“…SiO: Gusdorf et al 2008;Anderl et al 2013), the double-Gaussian decomposition of the OH line profiles (Sect. 4.1) fails to account for the complexity of the observed emission.…”
Section: Scenario 1: One Outflow Two Shock Layersmentioning
confidence: 99%
“…Guillet et al 2009Guillet et al , 2011. Anderl et al (2013) have shown that including them does not significantly alter the predicted OH emission of C-type models with n H of the order of 10 5 cm −3 (see their Fig. B.4), but that it does affect the shape of the predicted energy distribution of the CO spectral line (see their Fig.…”
Section: Scenario 1: One Outflow Two Shock Layersmentioning
confidence: 99%